The Position of Inheritance Rights of Children Out of Wedlock According to the Perspective of Civil Law - Aprilatama, Moh. Misandi Yoga (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The purpose of research from this journal is to determine the position of children out of wedlock in the inheritance law that applies in Indonesia. The problem regarding inheritance law is about what and how the obligations and rights regarding a person's wealth when he dies are to be given to the recipient. Thus, one aspect of inheritance is the existence of heirs who have the right to obtain certain assets from death. To decide who will get the wealth from death (the beneficiaries) is usually decided by certain legal rules of society or cultural laws applied by certain ethnic groups. The research method used is normative legal research method. Children out of wedlock that can be recognized are based on Article 272 B.W, namely: those born to a mother but who are not conceived by a man who is in a legal marriage bond with the child's mother, and are not classified as a group of adulterous children and illegitimate children.Keywords: Children; Inheritance; Rights; Wedlock.